AI-Powered Behavioral Analytics in Mental Health Developing Predictive Models for Therapy Outcomes - Dr. S. Uma; Mrs D. Sharmila; ARAVINDHAN B; CHIBHIRAJ S; ASWINI V (The Bioscan, 2025)
Traditional assessment and treatment approaches for mental health disorders use subjective evaluations to serve millions of affected individuals across the world. AI advances as well as behavioral analytics systems allow the healthcare field to gain more data-based insights about patient recovery together with therapy results. Behavioral analytics technology enhanced by artificial intelligence is evaluated for its effectiveness in forecasting therapy result outcomes. Machine learning models detect treatment efficiency through the analysis of multiple data sources that consist of speech vocalizations and facial behaviors and physiological body indicators.